(untitled) (Advances in Civil and Architectural Engineering, 2023)
This study analytically investigates the behaviour of trapezoidal infilled frames (TIFs) with brick masonry infills having openings and various interface materials between the brick panel and reinforced concrete frame. Single-storey single-bay frame specimens are analysed under in-plane static loading. For this investigation, the optimum angle of the column inclination for the trapezoidal frame must be determined in terms of maximum lateral stiffness. The optimum angle must be further analysed and compared with rectangular bare and infilled frames, with various materials of the interface. This infilled frame is extended to analyse the openings in the infill further. To study the effects of openings in infilled panels, TIFs with different sizes and positions of window openings are analysed and compared with the rectangular frame. This study further analyses three different combinations of interfaces and determines the intermediate stiffness of the frame combination. The main focus of this investigation is to reduce the high rigidity of the TIF leading to high base shear. It is found that, the infilled frame is stiffer than the bare frame, and the cement mortar interface is stiffer than the lead–cork interface. This research uses ABAQUS software, a finite element analysis program, for expanding the observational analysis.